Emerging Technologies in Spinal Surgery: Ultra-Low Radiation Imaging Platforms. (15th June 2021) - Pacult, Mark A; Walker, Corey T; Godzik, Jakub; Turner, Jay D; Uribe, Juan S
Abstract: BACKGROUND: Spine surgery has seen tremendous growth in the past 2 decades. A variety of safety, practical, and market-driven needs have spurred the development of new imaging technologies as necessary tools for modern-day spine surgery. Although current imaging techniques have proven satisfactory for operative needs, it is well-known that these techniques have negative consequences for operators and patients in terms of radiation risk. Several mitigating techniques have arisen in recent years, ranging from lead protection to radiation-reducing protocols, although each technique has limits. A hitherto-problematic barrier has been the fact that efforts to diminish radiation emission come at the cost of reduced image quality. OBJECTIVE: To describe new ultra-low radiation imaging modalities that have the potential to drastically reduce radiation risk and minimize unacceptable adverse effects. METHODS: A literature review was performed of articles and studies that used either of 2 ultra-low radiation imaging modalities, the EOS system (EOS-Imaging S.A., Paris, France) and LessRay (NuVasive, San Diego, CA). RESULTS: Both ultra-low radiation imaging modalities reduce radiation exposure in the preoperative and perioperative settings. EOS provides 3-dimensional reconstructive capability, and LessRay offers intraoperative tools that facilitate spinal localization and proper visual alignment of the spine. CONCLUSION: These novel radiation-reducing technologies diminish patient and surgeon exposure, aid the surgeon in preoperative planning, and streamline intraoperative workflow.